2019
DOI: 10.1017/jfm.2019.416
|View full text |Cite
|
Sign up to set email alerts
|

Richtmyer–Meshkov instability on a quasi-single-mode interface

Abstract: Experiments on Richtmyer–Meshkov instability of quasi-single-mode interfaces are performed. Four quasi-single-mode air/$\text{SF}_{6}$ interfaces with different deviations from the single-mode one are generated by the soap film technique to evaluate the effects of high-order modes on amplitude growth in the linear and weakly nonlinear stages. For each case, two different initial amplitudes are considered to highlight the high-amplitude effect. For the single-mode and saw-tooth interfaces with high initial ampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 45 publications
1
67
0
1
Order By: Relevance
“…The mode coupling in the dual-mode RMI with two basic waves of equivalent amplitudes acts earlier and more evidently than that of the multi-mode RMI with an initial dominant mode (Liang et al. 2019). The mode coupling process revealed in the dual-mode RMI would be of great use for understanding and modelling the multi-mode RMI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mode coupling in the dual-mode RMI with two basic waves of equivalent amplitudes acts earlier and more evidently than that of the multi-mode RMI with an initial dominant mode (Liang et al. 2019). The mode coupling process revealed in the dual-mode RMI would be of great use for understanding and modelling the multi-mode RMI.…”
Section: Discussionmentioning
confidence: 99%
“…Further, we performed experiments on quasi-single-mode interfaces formed by the same soap-film technique (Liang et al. 2019). It was found that the fundamental mode dominates the initial quasi-single-mode interface and, consequently, the effect of high-order modes on the amplitude growth can be ignored in the linear stage.…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that, although can be approximated using the impulsive model of Richtmyer (1960), the reduction factor in this model can vary significantly with different initial conditions (see Liang et al. 2019).…”
Section: Simulation Overviewmentioning
confidence: 99%
“…(2009) and experimental data of Jacobs & Krivets (2005) and Liang et al. (2019) with key parameters summarized in table 4.…”
Section: Modelling Of Spike and Bubble Growth Ratesmentioning
confidence: 99%
“…激波诱导界面不稳定性, 又称为激波与界面相互 作用或Richtmyer-Meshkov (RM)不稳定性, 最早是由 Richtmyer [1] 在1960年做出理论预测, 并由Meshkov [2] [3] 、航天火箭发动机 [4] 、天体物理 [5] 等领域有着重要的研究和应用价值. 如, 它是惯性约束 [6][7][8][9][10][11][12][13][14][15][16][17][18][19] , 我国 学者也开展了丰富的研究工作并取得一系列重要进 展 [20][21][22][23][24][25][26][27][28][29] . 近年来, 相关的专题综述已经4次在Annual Review of Fluid Mechanics上发表 [30][31][32][33] .…”
Section: 引言unclassified